Preparation of Tween 80-Zn/Al-levodopa-layered double hydroxides nanocomposite for drug delivery system - Kura, Aminu Umar; Hussein Al-Ali, Samer Hasan; Hussein, Mohd Zobir; Fakurazi, Sharida (Hindawi Publishing Corporation, 2014)
We incorporated anti-Parkinsonian drug, levodopa (dopa), in Zn/Al-LDH by coprecipitation method to form dopa-LDH nanocomposite. Further coating of Tween-80 on the external surfaces of dopa-LDH nanocomposite was achieved through the oxygen of C=O group of Tween-80 with the layer of dopa-LDH nanocomposite. The final product is called Tween-dopa-LDH nanocomposite. The X-ray diffraction indicates that the Tween-dopa-LDH nanocomposite was formed by aggregation structure. From the TGA data, the Tween-80 loading on the surface of LDH and dopa-LDH was 8.6 and 7.4%, respectively. The effect of coating process on the dopa release from Tween-dopa-LDH nanocomposite was also studied. The release from Tween-dopa-LDH nanocomposite shows slower release compared to the release of the drug from dopa-LDH nanocomposite as done previously in our study, presumably due to the retarding shielding effect. The cell viability study using PC12 showed improved viability with Tween-80 coating on dopa-LDH nanocomposite as studied by mitochondrial dehydrogenase activity (MTT assay).